2017
DOI: 10.1055/s-0037-1604282
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Extraction of a Needle from the Internal Carotid Artery: A Novel Approach to a Controversial Dental Misadventure

Abstract: Objective  To review the literature concerning the management of dental needles broken off into the deep spaces of the neck, to report what we believe is the first case of a fractured dental needle migrating into the jugular foramen, and the unconventional use of endovascular intervention to retrieve the needle fragment. Design  Case report with review of literature. Setting  Academic tertiary care center. Participants  Intervention was performed by the otolaryngology–head and neck surgery, vascular surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…Successful removal of the needle was ultimately accomplished with a microsnare and balloon catheter during a cerebral angiogram. 2 The anatomic location of the broken needle and its metallic nature somewhat parallels the incident described in the present case report.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Successful removal of the needle was ultimately accomplished with a microsnare and balloon catheter during a cerebral angiogram. 2 The anatomic location of the broken needle and its metallic nature somewhat parallels the incident described in the present case report.…”
Section: Discussionsupporting
confidence: 77%
“…Regarding management of embedded hypodermic needles, Giurintano et al reported that retrieval under general anesthesia is the current recommendation, noting that delay in retrieval can result in migration of the foreign object. 2 Intraoperative CT or fluoroscopy is recommended to guide surgical retrieval procedures. The lack of evidence of migration of the archwire fragment in the case of our first patient supports the surgeons' recommendation to not attempt retrieval at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Лечение. На основании данных, полученных нами при обзоре литературы, лечение проводят двумя способами: 1) экстренная госпитализация; 2) наблюдение и последующее оперативное лечение [1,3,[9][10][11][12][13][14]. Преимущества того или иного метода нами выявлено не было, однако каждый из способов имеет право на применение.…”
unclassified